A new, optimized Doppler optical probe for phase detection, bubble velocity and size measurements: Investigation of a bubble column operated in the heterogeneous regime. (15th March 2022) - Lefebvre, Anthony; Mezui, Yann; Obligado, Martin; Gluck, Stéphane; Cartellier, Alain
Graphical abstract: Highlights: A new optical sensor for bubble velocity and size measurements is proposed. The sensor gives the bubble translation velocity projected along the fiber axis. Reliable data are collected in a bubble column up to 30% global gas holdup. A self-similar bubble velocity profile is established in the heterogeneous regime. Bubble turbulent vertical intensity reached 55% in the heterogeneous regime. Abstract: A new technique dedicated to bubble velocity and size measurements in complex bubbly flows is proposed. This sensor combines the phase detection capability of a conical optical fiber with velocity measurements from the Doppler signal induced by an interface approaching the fiber extremity. It provides the translation velocity of bubbles projected along the probe axis with an uncertainty at most 14%. This sensor has been successfully exploited in a 0.4 m diameter bubble column. In the heterogeneous regime, the mean bubble velocity profiles scaled by the value on the axis are shown to be self-similar in the quasi fully developed region of the column. Besides, the standard deviation of bubble velocity scaled by the mean velocity increases with Vsg in the homogeneous regime, and it remains stable, close to 0.55, in the heterogeneous regime. Such a sensor opens the way to velocity measurements conditioned by the local void fraction.